Preparation method of friction-resistant anti-icing coating

Through multi-level preparation methods, including self-healing the bottom layer, hydrophobic middle layer and nano-microstructure upper layer, the problems of performance degradation and insufficient durability of the anti-ice coating under extreme conditions are solved, and higher wear resistance and ice resistance are achieved Adhesion.

CN119281623APending Publication Date: 2025-01-10XIAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411378885.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing anti-ice coatings are prone to performance decline, cracks and wear under extremely low temperatures, high humidity, ultraviolet irradiation and rapid mechanical stresses, resulting in insufficient durability.

Method used

Multi-level preparation methods, including surface pretreatment to obtain a clean activated substrate, forming a bottom layer with self-healing function, depositing a fluoropolymer mid-layer to provide hydrophobicity, and providing nano-microstructure upper layers on the surface to enhance mechanical properties and anti-ice stickiness Adhesion.

Benefits of technology

It effectively solves the problem of deterioration in performance and insufficient durability of the coating under complex conditions, improves the wear resistance and ice adhesion of the anti-ice coating, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281623A_ABST
    Figure CN119281623A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anti-icing coatings, and discloses a preparation method of a friction-resistant anti-icing coating, which comprises the following steps: obtaining a clean activated substrate based on surface pretreatment; forming a bottom layer with a self-repairing function; depositing a fluoropolymer intermediate layer to provide hydrophobicity; and the nano microstructure upper layer is arranged to enhance the mechanical property and the ice adhesion resistance. Through a multi-level strategy including a self-repairing mechanism of a bottom layer, effective isolation of a middle layer on environmental moisture and a design scheme of a surface structure for resisting physical stress, the problem that the coating faces complex conditions and is difficult to repair is comprehensively solved. In order to solve the problems of possible degradation of multiple functions and technical difficulties caused by cracks caused by low-temperature brittleness, bonding failure caused by excessive humidity, separation of the material in repeated temperature change, performance reduction caused by aging and abrasion under the action of ultraviolet rays, and the like, the base material is in a clean and activated state by adopting a proper technical means, so that the service life of the base material is prolonged. Therefore, the adhesive force between the coating and the base material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-icing coatings, and in particular to a method for preparing a friction-resistant anti-icing coating. Background Art

[0002] A method for preparing a friction-resistant anti-icing coating for improving the performance of structural materials in harsh environments generally involves coating a material with low surface energy and micro-nanostructure characteristics on a substrate through a specific process to reduce the adhesion of ice and enhance the wear resistance of the surface;

[0003] However, although this technology can provide effective anti-icing and wear protection under certain conditions, there are still some challenges to be faced: first, in extremely low temperature environments, the brittleness of the coating material may increase as the temperature decreases, causing the material to easily crack and thus affect its overall performance; in addition, in high humidity environments, such coatings may also absorb water, weakening the adhesion between them and the substrate; at the same time, after experiencing multiple freeze-thaw processes, due to the difference in thermal expansion coefficients between the coating and the base layer, the two may be delaminated or even completely peeled off; secondly, when exposed to ultraviolet rays for a long time, the physical and chemical properties of the coating will deteriorate, reducing its protective performance; finally, when frequently subjected to rapid mechanical stress, the coating may accelerate wear and thus reduce its service life, which not only affects the functional performance of the coating itself, but also affects the overall stability and durability of the entire material or structure. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a friction-resistant anti-icing coating, which solves the problem of protective performance degradation caused by coating surface aging in the background technology and the problem of insufficient durability caused by coating wear during high-frequency rapid friction.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a friction-resistant anti-icing coating comprises the following steps:

[0007] S1: obtaining a clean activated substrate based on surface pretreatment;

[0008] S2: Forming a bottom layer with self-repairing function;

[0009] S3: depositing a fluoropolymer middle layer to provide hydrophobicity;

[0010] S4: Setting a nano-microstructured upper layer to enhance mechanical properties and anti-ice adhesion.

[0011] Preferably, the specific steps of obtaining a clean activated substrate based on surface pretreatment include:

[0012] S101: Clean the substrate to remove contaminants;

[0013] S102: Mechanically polish or chemically treat the substrate surface to activate the surface;

[0014] S103: Further clean and roughen the surface by sandblasting to improve the adhesion of the subsequent coating;

[0015] S104: Preheat the substrate to a temperature T1, where T1 is between the ambient temperature Tamb and the critical temperature Tc, ensuring T1 < Tc. Here, T1 refers to the preheating temperature, and Tc refers to the temperature threshold to avoid the material from starting to soften or deform due to excessive heating. This helps prevent crack propagation caused by increased brittleness of the coating material at extremely low temperatures.

[0016] Preferably, the sandblasting process in the surface pretreatment includes:

[0017] A1: Use particles with an average particle size d1, and the particle size is controlled within the range of dmin to dmax, where 2mm ≤ dmin ≤ d1 and dmax = 2 * d1;

[0018] A2: Set the pressure P of the compressed air to be adjusted between 1 and 2 atmospheres to control the impact speed;

[0019] A3: Adjust the distance between the abrasive and the substrate to D;

[0020] A4: The ratio of d1 / P is adjusted to ensure an appropriate abrasive erosion rate to optimize the surface texture. This ratio should satisfy the condition d1 / P ≤ dmax * D / (Tc - Tamb). This formula is used to calculate the proportional relationship between the particle size and the compressed air pressure during sandblasting to achieve the most suitable coating pretreatment effect under different ambient temperature conditions.

[0021] Preferably, the selection of the sandblasting medium during sandblasting includes:

[0022] Select suitable hard particles according to the material;

[0023] Prevent moisture condensation by measuring and ensuring that the dew point temperature of the compressed air is below zero;

[0024] Pre-dry the abrasive to remove impurities and ensure its purity;

[0025] Ensure that the abrasive particle size used meets the requirements calculated by the previous formula, and adjust the selection of abrasive particles d1 so that the degree of wetness of the abrasive before reaching the substrate during flight in compressed air does not exceed a specific threshold Wt (where Wt is defined as the maximum allowable ratio of the moisture content in the air to the dry air mass), ensuring the effective dryness of the sandblasting process and reducing problems caused by water absorption under high humidity conditions.

[0026] Preferably, based on the abrasive particle selection and the air moisture content conditions:

[0027] Particles with an average diameter of X millimeters are selected;

[0028] Set the humidity in the compressed air not to exceed a predetermined standard Y%, where Y represents the maximum acceptable level of the environmental relative humidity;

[0029] Verify the substrate temperature difference range before actual spraying to avoid peeling caused by the mismatch of the expansion coefficients between the coating and the substrate due to the temperature difference;

[0030] Set the correlation condition between X and the water content Z in the compressed air: X < f(Y,Z), where f represents a correction function established based on laboratory data, which ensures that the matching of the physical properties of the particles and the humidity of the operating environment does not reduce the bonding strength between the coating and the substrate.

[0031] Preferably, based on adjusting the correlation coefficient between the water content of the compressed air and the particle size:

[0032] Control the particle spraying rate so that the thickness of the coating per unit area remains consistent each time;

[0033] Adjust the air cooling time and frequency to ensure stress release during the pretreatment process to prevent cracking;

[0034] Detect the relative humidity of the air to adjust the water content ratio in the sandblasting material and the compressed air in real time;

[0035] Define the correlation condition between X and Z so that the compressed air quality level is higher than a specific level S (where S refers to the designated level of a certain part of the ISO8573 compressed air standard) to ensure that the coating preparation quality is not affected by moisture, and when X reaches a certain size threshold, add dehydration facilities at the nozzle to reduce Z to meet the requirements of high-specification preparation standards.

[0036] Preferably, the process of obtaining a clean and activated substrate based on surface pretreatment includes:

[0037] Ultrasonic cleaning to remove impurities on the substrate surface;

[0038] Use pickling or alkali washing treatment to improve surface activity;

[0039] Adopt plasma treatment to enhance the adhesion of the substrate; and

[0040] Dry at below 50 degrees Celsius to prevent re-contamination of the surface.

[0041] Preferably, the process of forming the bottom layer with self-repairing function comprises:

[0042] The ability of the coating to automatically recover broken bonds based on the coating of polyurea elastomer;

[0043] Mixing in reversibly cross-linkable monomers to enhance the ductility of the material at low temperatures;

[0044] Adding UV stabilizers to resist chemical bond scission under light; and

[0045] The interface between the layers is designed to accommodate different thermal expansion coefficients TCE (TCE stands for Thermal Coefficient of Expansion) and to ensure stress relaxation when TCE_coating ≠ TCE_substrate.

[0046] Preferably, the process of depositing the fluoropolymer middle layer comprises:

[0047] Use vapor deposition process to ensure uniform coating and reduce irregular cracks;

[0048] Adjust the ratio RF of fluoropolymer to solvent during spraying (RF stands for Ratio of Fluoropolymer to Solvent). When RF> the set ratio threshold, the water absorption is reduced.

[0049] High temperature rapid curing of coatings to improve mechanical strength;

[0050] The characteristics of fluorine atoms are used under high temperature conditions to improve the wear resistance and hydrophobicity of the surface.

[0051] Preferably, the process of setting the nano-microstructure upper layer enhancement specifically includes:

[0052] Based on nanoparticle embedding technology, the surface friction is optimized to enhance the wear resistance NWD (NWD refers to NanoWearDurability). When NWD < target wear resistance value, the distribution concentration of particles needs to be increased to improve wear resistance;

[0053] Forming a nanoporous network to enhance microscopic roughness;

[0054] Evaporation of nano-scale thin films improves the peeling strength of the upper layer;

[0055] Pulsed laser deposition is used to prepare surface topologies with complex structures, multiple pores and highly controllable size characteristics, thereby effectively reducing ice viscosity.

[0056] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0057] 1. Through a multi-level strategy, including the self-repair mechanism of the bottom layer, the effective isolation of the middle layer from environmental moisture, and the design of the surface structure to resist physical stress, the coating is fully resolved to face complex conditions, such as cracks caused by low-temperature embrittlement, adhesion failure caused by excessive humidity, detachment of materials during repeated temperature changes, aging under ultraviolet rays, and performance degradation caused by wear and tear. Multiple functional degradation and technical difficulties that may occur under these conditions are fully resolved.

[0058] 2. By using appropriate technical means to clean and activate the substrate, the adhesion between the coating and the substrate is enhanced. Then a self-healing bottom layer is formed. This special bottom layer can automatically heal cracks when the coating surface is slightly damaged, significantly improving the ability of the anti-icing coating to resist crack propagation caused by material embrittlement under extreme cold conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is a flow chart of a method for preparing a friction-resistant anti-icing coating;

[0060] Figure 2 It is a flow chart for obtaining a clean activated substrate based on surface pretreatment;

[0061] Figure 3 It is based on the flow chart of the sandblasting process package in surface preparation;

[0062] Figure 4 It is a flow chart based on the selection of blasting media when blasting;

[0063] Figure 5 It is a flow chart based on the abrasive grain selection and air moisture content conditions;

[0064] Figure 6 It is a flow chart based on adjusting the correlation coefficient between the moisture content of compressed air and the particle size;

[0065] Figure 7 is a flow chart of the process of obtaining a clean activated substrate based on surface pretreatment;

[0066] Figure 8 is a flow chart of a process of forming a bottom layer having self-healing capabilities;

[0067] Fig. 9 is a flow chart of a process for depositing a fluoropolymer middle layer;

[0068] Fig.10 It is a specific flow chart for setting the nano-microstructure upper layer enhancement process. DETAILED DESCRIPTION

[0069] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] The present invention provides a method for preparing a friction-resistant anti-icing coating, the purpose of which is to overcome a series of challenges faced by traditional anti-icing coatings through a series of design and preparation methods, including performance degradation under extreme conditions, durability under high humidity conditions, and stability under repeated temperature differences.

[0071] First, it is necessary to ensure that the quality and performance of the substrate surface match the application of the coating, and to achieve full purification and activation of the substrate through effective surface pretreatment, which involves removing surface contaminants and forming chemically activated areas. In this process, various pretreatment technologies can be applied, such as plasma treatment, laser cleaning or chemical etching. The selection of these technologies not only removes surface oil, oxides and other dirty substances, but also may expose a fresh layer of the substrate and give a certain micro-roughness, which is beneficial to improve the mechanical interlocking effect between the subsequent coating and the substrate, thereby improving the adhesion quality of the coating. At this stage, it is crucial to choose a suitable method to pretreat the substrate, because if the surface is not effectively purified, good adhesion between the coating and the base layer cannot be achieved, thereby affecting the overall effect of the anti-icing coating; for example, in one embodiment, a low-frequency plasma cleaner is used to treat the metal surface so that the microscopic morphology of the substrate is more conducive to the subsequent layer to combine with it.

[0072] Next is the bottom layer link of forming the self-healing function. In this process step, the coating is designed to have the ability of self-recovery. Even if it is damaged, it can fill the cracks by itself to maintain its integrity. This is achieved by adding a specific chemical reaction system to the coating. For example, in some cases, you may choose to embed capsules or other packaging methods to add composite materials containing healing agents into the coating. When damage occurs, the capsule ruptures due to external force and releases healing substances for self-healing. It prevents the cracks from spreading further and solves the problem of materials becoming brittle and cracking under low temperature conditions.

[0073] The next step is to use fluoropolymer as the core component of the coating to deposit an intermediate coating with a highly hydrophobic effect and abrasion resistance. This step is crucial and its purpose is to give the entire coating ice repellency. Since fluorochemicals have unique surface properties that can significantly reduce the force of liquid water and ice crystals on the contact surface, they can effectively resist the formation of ice nuclei and reduce the possibility of icing. The introduction of fluoropolymers effectively alleviates the problem of decreased adhesion caused by increased humidity and improves the moisture protection function of the coating. Specifically, a layer of material containing multi-level fluorine chain structure molecules can be evenly coated on the treated and attached self-healing matrix through CVD or PVD deposition process to form a basic protective layer of the anti-icing coating to ensure that it still maintains a certain strength and service life even under humid environmental conditions, and is not prone to delamination or loss of effectiveness. In actual application cases, plasma polymerization is usually used to generate a super-hydrophobic smooth film containing FC to ensure that the cohesive energy between the coating and the water droplets is less than the mutual attraction between the two, thereby achieving the expected low contact angle and efficient water repellency.

[0074] Finally, in order to enhance the mechanical stability of the anti-icing coating, the nano-microstructure surface treatment is used. This process aims to improve the overall structural characteristics of the coating and increase its friction resistance and pull-out resistance. By introducing a microstructure with a specific nanoscale (such as complex morphologies such as homogeneous particles, columns or tubes), it is possible to provide excellent friction characteristics without changing the overall geometric volume size of the coating; nanoparticles not only help to reduce the surface roughness value, but also maintain the original integrity of the coating under repeated hot and cold cycles to prevent peeling problems. At the same time, it can also resist the surface degradation caused by UV rays, thereby increasing the life of the coating. For example, using nano-silicon dioxide as an additive to form a microcrystalline network on the pre-set middle and base layers not only improves the performance of the coating in terms of fatigue and wear resistance, but also maintains its proper performance after long-term exposure to sunlight, avoiding the dilemma of reduced protection efficiency. In addition, the unique low adhesion characteristics of the nanostructure can further improve the anti-icing effect, allowing ice crystals to slide off immediately when trying to land, and inorganic opportunities to stay on the protective surface, thereby ensuring that the coating has the functional characteristics of long-term effective resistance to damage caused by external factors.

[0075] Through the above steps, a new composite material solution that is both wear-resistant and durable against environmental damage is finally realized. It has broad prospects and application space in the fields of aviation, shipbuilding, transportation, and infrastructure. Especially in the harsh weather conditions in the north, it can give full play to its advantages and provide people with safe, reliable and worry-free technical support. At the same time, it also actively responds to the trend of modern society's ever-increasing demand for functional protective measures.

[0076] Next, the present invention is described to obtain a clean activated substrate based on surface pretreatment. Cleaning the substrate to remove contaminants is the first step of pretreatment, which aims to remove grease, dust, oxide layer and other impurities on the substrate that may interfere with the bonding strength of the coating by ultrasonic cleaning, solvent immersion or pickling, so as to improve the surface quality and coating performance. For example, in one embodiment, alcohol and an ultrasonic cleaner are used to completely remove impurities on the titanium alloy substrate to create conditions for the next process.

[0077] Mechanically grinding or chemically treating the substrate surface to activate the surface can produce a slight roughness on the substrate surface to promote the bonding force with the subsequent coating. Specifically, this can be achieved by polishing with sandpaper of different grits or by acid washing, thereby introducing functional active centers, improving surface energy, and enhancing chemical bonding. In a specific example, the stainless steel substrate is carefully polished with 1200 grit fine sandpaper to a uniform matte state to promote good adhesion with the subsequent coating.

[0078] Sandblasting is used to further clean and roughen the surface to improve the adhesion of subsequent coatings. It is based on the previous step to use high-pressure air to drive abrasive particles of a certain size to spray the substrate surface to increase its roughness. This not only removes tiny residues, but also forms a structure that is conducive to the embedding of the coating, thereby improving the mechanical properties of the final coating system. For example, during the preparation of the friction-resistant coating, silica beads may be selected to sandblast the surface of the aluminum plate at a pressure of 3 Pascals.

[0079] Preheat the substrate to temperature T1. A preheating stage needs to be set here to raise the substrate temperature to a certain level without damaging the substrate itself. T1 should be selected to be lower than the temperature (Tc) at which the substrate material begins to soften, to ensure that the material is not damaged when the coating is cured. It also takes into account that the friction-resistant coating used in low-temperature environments should have good low-temperature resistance to prevent the risk of cracks caused by increased brittleness due to sudden temperature drops. For example, before applying a polyamide resin-based anti-icing coating to a steel substrate, the substrate is preheated to about 110 degrees Celsius to ensure that it does not exceed the maximum heat treatment temperature that this type of steel can withstand without permanent shape changes (Tc may be between about 250 and 300 degrees Celsius). This setting also takes into account the application of the material in a sub-freezing environment, effectively balancing the needs of anti-slip and crack resistance.

[0080] Next, the sandblasting process in the surface pretreatment of the present invention is described, which includes: using particles with an average particle size of d1, and the particle size is controlled within the range of dmin to dmax, wherein 2mm≤dmin≤d1, and dmax=2*d1; setting the pressure P of the compressed air to be adjusted between 1 and 2 atmospheres to control the impact speed; adjusting the distance between the abrasive and the substrate to D; wherein the ratio d1 / P is adjusted to ensure an appropriate abrasive erosion rate to optimize the surface texture, and this ratio should satisfy the condition d1 / P≤dmax*D / (Tc Tamb), which is used to calculate the proportional relationship between the particle size and the compressed air pressure during the sandblasting process, so as to achieve the most suitable coating pretreatment effect under different ambient temperature conditions.

[0081] The use of specific abrasive sizes during sandblasting is to ensure the effectiveness of the pretreatment process. The abrasive particles must have a specific particle size d1, as well as the corresponding upper and lower limits dmin and dmax. The 2mm here represents the minimum possible size dmin that must be achieved at least, and this dmin cannot exceed the selected average particle diameter d1. The dmax refers to the maximum particle size, which is specified as twice the average particle size. This is to ensure that all abrasive particles can provide sufficient impact force and produce a uniform and consistent surface effect under the predetermined pressure conditions.

[0082] The selection of compressed air pressure P is also extremely important and needs to be controlled within a certain range to ensure the appropriate abrasive speed to obtain the required roughness and cleaning degree. The pressure P selected in this process should be in the range of one to two atmospheres, so as to accurately adjust the speed and energy of the collision according to different needs.

[0083] In addition, the distance D from the abrasive to the surface of the substrate must be set, which determines the distribution of abrasive particles in the jet and the density of abrasive particles reaching the workpiece surface. This distance affects the impact strength and efficiency, so D needs to be appropriate.

[0084] A key in this process is to adjust the d1 / P ratio to ensure the appropriate erosion rate to optimize the surface texture and roughness of the material. In order to meet the constraints of the condition d1 / P≤dmax*D / (Tc Tamb) to achieve the best results, the ratio needs to be carefully calibrated. Tc represents the critical temperature control coefficient near the working surface or the processing surface, while Tamb reflects the ambient temperature conditions. In this way, the optimal configuration required in the spraying process is calculated to ensure that the ideal processing effect can be achieved regardless of the change in ambient temperature.

[0085] In a specific embodiment, for the pretreatment of the anti-friction and anti-icing coating on the outer layer of an aviation component, assuming that d1 is selected to be about 0.6 mm, dmin shall not be less than 2 mm and not more than 0.6 mm; accordingly, dmax is set to 1.2 mm. In order to obtain the ideal surface quality, the pressure P may be set at one and a half atmospheres, and at the same time the working distance D between the substrate and the nozzle may be adjusted to a suitable size such as 15 cm, so that the appropriate spraying texture can be obtained under different ambient temperature conditions. According to the given conditions and the required d1 / P≤dmax*D / (Tc Tamb) calculation results, the coating has excellent adhesion and anti-icing function.

[0086] This design ensures that even if the environment changes, the final coating can still achieve good pretreatment under various conditions, thereby enhancing the performance of the overall material or structure.

[0087] Next, the present invention describes the selection of blasting media based on sandblasting. Sandblasting is a process used for surface treatment. Choosing the right blasting material can affect the surface cleaning effect and the adhesion performance of the subsequent coating. The selection of media in the sandblasting process requires careful consideration. The following steps are the specific process:

[0088] Choosing the right hardness particle for the material means choosing particles of appropriate hardness to match the material characteristics of the substrate to avoid excessive damage or insufficient cleaning. For example, for soft steel materials, steel shot can be used as an abrasive. If you need to clean more sensitive or fragile materials, such as aluminum, you should choose a relatively soft abrasive such as nylon shot.

[0089] Ensuring that the air system is dry is a key step in preventing moisture condensation. Since the moisture contained in compressed air will condense into liquid at a lower temperature, it may cause re-contamination of the metal surface in the working environment, thereby weakening the effect of the anti-icing coating. Usually, a monitoring system is used to ensure that the dew point temperature of the compressed air is maintained below an appropriate level to keep the system sufficiently dry. In one embodiment, the compressed air should have a dew point temperature tested at a standard temperature of no more than -40°C.

[0090] To ensure the purity and quality of the abrasive, it is essential to dry the blasting media before use to remove any moisture and other impurities that may be present. Specifically, the abrasive can be heated in an oven before use to remove the moisture contained in it. This helps to improve the quality of the blasting and ensure that the coating can be evenly and reliably bonded to the surface.

[0091] When determining the abrasive particle size, it is crucial to consider the impact of moisture on the process. To this end, calculate the degree of wetness of the abrasive under specific conditions and control it within a specific value Wt. Here, it is assumed that the maximum allowable ratio of Wt is 0.03%, which represents the upper limit of the allowable moisture content ratio. Such a practice helps to ensure environmental control during the coating preparation process, especially in a high-humidity environment, and can effectively reduce problems caused by the abrasive medium coming into contact with moisture. The formula ensures that the particles remain fully dry when flying towards the workpiece surface and helps to form a more consistent and stronger coating adhesion, ultimately improving the effect of the friction and icing-resistant coating. For example, if the environmental conditions cause excessive humidity in the air, the abrasive diameter can be preset and the density of the abrasive can be appropriately increased to compensate for the additional wetting effect. Such adjustments enable the process to meet strict quality requirements and maintain the best process results.

[0092] Next, describe the abrasive particle selection and air moisture content conditions of the present invention: Particles with an average diameter of X millimeters are selected; the humidity in the set compressed air does not exceed the predetermined standard Y%, where Y represents the maximum acceptable level of the environmental relative humidity; verify the substrate temperature difference range before actual spraying to avoid peeling caused by the mismatch of the expansion coefficients between the coating and the substrate due to the temperature difference; set the correlation condition between X and the water content Z in the compressed air: X < f(Y, Z), where f represents a correction function established based on laboratory data, which ensures that the matching of the physical properties of the particles and the humidity of the operating environment will not reduce the bonding strength between the coating and the substrate.

[0093] The first step involves the selection of particles. In this step, abrasive particles with an average diameter marked as X are selected. This step is crucial for the coating process because abrasives of different sizes will affect the quality of the sprayed coating, especially the surface roughness, density, and bonding strength of the coating. X should be determined according to the required function and the type of surface treatment. In one embodiment, when high bonding strength and low porosity are desired, medium-diameter particles, such as 50-micron silica or diamond, may be preferentially selected.

[0094] Immediately following is the second step of controlling the humidity level of the compressed air. Excessive humidity in the compressed air will affect the coating process, especially in thermal spraying, which will lead to the formation of coating defects. Y defines the highest level of allowable relative humidity. Generally, the relative humidity should be strictly controlled at a lower level, such as 30%. During actual operation, a drying device is used to reduce the moisture content in the compressed air and keep its humidity always lower than the preset standard Y.

[0095] Next, before applying the coating formally, the difference between the temperature of the substrate and the spraying operation temperature is carefully verified to control the temperature difference. This is to prevent thermal strain between the coating and the substrate due to inconsistent temperatures or problems such as cracks or peeling caused by temperature-induced stress. A specific example of this step could be to confirm that the temperature difference between the substrate and the spraying nozzle does not exceed a pre-set safety value before spraying to ensure consistent expansion or contraction behavior of the material. For example, in one embodiment, it may be specified that the temperature difference should not exceed 20 °C.

[0096] Finally, a relationship model between the X-diameter particles and the water content Z in the compressed air is established: that is, when X < f(Y, Z). f(Y, Z) is a mathematical relationship expression obtained by fitting the data obtained under laboratory conditions, and this expression shows the regulating effect of the air water content on the upper limit of the jet particle diameter. For example, f may be a function of the minimum particle diameter that ensures the best bonding under a given humidity condition as shown by experimental data. Through this formula, it is ensured that appropriate-sized particles are selected for coating treatment at any specific environmental humidity to prevent problems such as large particles changing shape due to moisture absorption or reduced adhesion performance at higher humidities.

[0097] Therefore, the whole method is an effective way to ensure the quality and durability of the coating, especially important in application environments that need to resist freezing conditions and require wear resistance at the same time. For example, the wing surfaces of aircraft need such coatings to cope with extreme climate changes and the friction caused by long flights.

[0098] Next, the correlation coefficient based on adjusting the water content of the compressed air and the particle size in the present invention is described: controlling the particle spraying rate to keep the thickness of the coating layer per unit area consistent each time; adjusting the air cooling time and frequency to ensure stress release during the pretreatment process to prevent cracking; detecting the relative humidity of the air to adjust the water content ratio in the abrasive blasting material and the compressed air in real time; defining the correlation condition between X and Z to make the compressed air quality level higher than a specific level S (here S refers to the specified level of a certain part of the ISO8573 compressed air standard) to ensure that the coating preparation quality is not affected by moisture, and when X reaches a certain size threshold, adding dehydration facilities at the nozzle to reduce Z to meet the requirements of high-specification preparation standards.

[0099] Control the particle spraying rate to keep the thickness of the coating layer per unit area consistent each time. This means maintaining the consistency of the coating by precisely controlling the number and speed of the particles used during the spraying process, thereby ensuring that each coating layer has a predetermined and controllable thickness. In one embodiment, when spraying an anti-icing coating with wear resistance, by controlling the speed and density of the particles, the coverage rate per square meter is a certain kilogram value to obtain the same coating film thickness and ensure the uniformity and strength of the coating.

[0100] Adjust the air cooling time and frequency to ensure stress release during pretreatment to prevent cracking. It is emphasized here that in order to reduce the risk of coating cracking caused by thermal stress generated by temperature changes inside the substrate material, the time and frequency of the cooling process must be appropriately adjusted. Specifically, before preparing for spraying, a series of thermal expansion and contraction treatment cycles may be performed to relax internal stress. If the material is cooled or heated too suddenly, the residual thermal stress inside may cause cracks on the coating surface.

[0101] Detect the relative humidity of the air to adjust the water content ratio of the blasting material and compressed air in real time. This step is to reduce the negative impact of excessive humidity on coating performance. For example, when depositing a special functional composite coating that is wear-resistant and anti-icing, a high humidity environment may make the final coating porous or uneven, so real-time detection and adjustment are necessary to achieve the best coating effect.

[0102] Define the relationship between X (range of blasting particle size) and Z (humidity content coefficient) to maintain the compressed air quality above the specified level S. For example, when preparing to spray ceramic microspheres with high durability and anti-ice and snow performance as a coating, in order to ensure that the coating will not fail due to external humidity, it is necessary to strictly control the quality of the compressed air to at least meet the third level of quality (i.e. no liquid, oil content <0.1mg / m 3 ), when it is detected that the particle X size is larger than a certain critical value, an additional dehydration unit is added to reduce the Z index to further remove factors that may affect the process results.

[0103] In the above stages, important variables such as acceptable particle size should be limited to micron level. Too large may damage the nozzle or form defects in the coating. The ideal state is to keep Z in a certain range such as ≤35%. This is because working in a relatively humid environment will cause more moisture to accumulate in the compressed air system, which is detrimental to the coating quality. By controlling the parameters within the optimal value, the coating quality can be significantly improved and the required technical specifications can be achieved.

[0104] Next, the process of obtaining a clean activated substrate based on surface pretreatment of the present invention is described. The process first involves using ultrasonic cleaning to remove impurities on the surface of the substrate. This step usually requires immersing the substrate in a solvent, such as deionized water or a chemical solvent suitable for a specific substrate material, to destroy the contamination layer on the substrate surface and in the micropores by generating a cavitation effect, thereby achieving an effective cleaning effect. For example, in a specific embodiment, in order to clean the surface of an aluminum alloy, deionized water suitable for the aluminum alloy material is selected as the cleaning solvent, and ultrasonic cleaning is performed at an ultrasonic frequency of 40 kHz for about 10 minutes.

[0105] The subsequent process is to treat the substrate with pickling or alkali washing to enhance its surface activity. This step can be accomplished by selecting an appropriate concentration of sulfuric acid or other acid or alkali solution suitable for the surface of a specific material. Specifically, when preparing a steel substrate, dilute sulfuric acid can be selected for pickling to increase the activity of the substrate surface while controlling the solution temperature and immersion time, so that it can better adsorb the anti-icing coating components. The solution in this process is usually configured to a concentration of 5%-20% (by mass fraction) and is best operated at room temperature to slightly elevated temperatures to avoid corrosion while ensuring reaction activity.

[0106] Next, plasma treatment is used to further increase the adhesion of the substrate to subsequent coating materials. In this process, the substrate is placed in a low-pressure environment and exposed to an excited gas plasma, which causes changes in the surface chemistry and morphology of the substrate material. For example, oxygen plasma treatment can be used for 5 minutes to optimize the adhesion of the substrate surface to the anti-icing material during application.

[0107] The last step is to dry the treated substrate at a relatively low temperature (below 50 degrees Celsius) to avoid thermal stress from damaging the substrate and prevent the re-adherence of pollutants to the surface during air cooling, thereby obtaining the best cleaning effect. Specifically, assuming that a ceramic substrate is used as the substrate material, due to the particularity of ceramics, drying under mild conditions within a temperature range of no more than 50 degrees Celsius can ensure that the material structure will not change and ensure the stability of its physical properties. This drying process may take about 30 minutes to complete.

[0108] It should be noted that the operating conditions mentioned throughout the process are examples and are adjusted by default based on actual equipment performance, material characteristics, process standards, etc., in order to improve the overall effectiveness of the final coating. No specific formula is provided here to adjust the process, but any specific values ​​or ranges mentioned can be regarded as best practices for achieving good coating adhesion and anti-icing performance.

[0109] Next, the process of forming a bottom layer with self-healing function of the present invention is described. The process includes several main steps to obtain a coating with friction-resistant and anti-icing properties, and with self-healing function. The first step involves a coating material based on a polyurea elastomer. Since polyurea has high strength, high flexibility and excellent adhesion, a layer formed on the surface can recombine itself after breaking through non-covalent forces between molecules. For example, in one application case, a polyurea base layer is prepared on an aluminum alloy substrate by a spraying method, which can heal itself when subjected to external damage (such as wear or slight scratches) to reduce crack expansion.

[0110] Next, reversible crosslinking monomers are mixed in as a second step to strengthen the structure of the polymer network, especially to provide sufficient flexibility without brittle fracture in low temperature environments. This is done by adding reversible crosslinking groups such as those with hydrogen bonding ability or weak van der Waals forces, which can recombine under certain conditions to increase the automatic recovery effect after fracture. For example, the reaction of diisocyanates with polyol compounds with such properties can effectively enhance the deformation and recovery properties of the material at low temperatures.

[0111] The addition of UV stabilizers is the third step, which is used to resist the potential destructive effects of ultraviolet rays on the internal bond structure of the coating material. Stabilizers are usually light-absorbing or free radical-trapping chemical additives that absorb ultraviolet light and convert it into a form that is less destructive to the coating material or prevent the formation of active free radicals. Specifically, benzophenone compounds are selected to add protection to the coating to reduce the damage to the material caused by sunlight and the reduction in lifespan, which is particularly critical for applications in outdoor environments, such as considering such factors in the design of protective layers on the surface of wind power equipment or solar cells.

[0112] The final step involves designing the appropriate interface properties between the coating and the substrate so that the material can compensate for the different thermal expansion coefficients between the two, ensuring that structural stresses remain within allowable limits and crack formation is avoided at different operating temperatures. When the thermal expansion coefficient of the coating material is significantly different from that of the metal substrate, an intermediate buffer layer is usually used to disperse the strain changes caused by heating or cooling. For example, before applying this anti-abrasion and anti-icing coating on carbon fiber reinforced plastic, a layer of epoxy resin is first applied to adjust the expansion difference between the two phases to ensure long-term stability and reliability. The key here is to select a transition layer with appropriate thickness and physical properties according to the specific situation so that the problems caused by the gap between the TCE coating and the TCE substrate can be effectively managed and controlled.

[0113] The above describes the role of each stage in the process of forming a self-healing bottom layer and its possible manifestations in actual engineering scenarios. The calculation of strain rate caused by differences in thermal expansion coefficients involves specific material properties, environmental conditions and expected product life. The optimal value depends on the data obtained under laboratory conditions and is obtained through appropriate model fitting optimization. For example, when it is known that the substrate material A has TCE_A, the TCE of the selected coating B needs to be accurately measured to obtain TCE_B before the type and size of the transition layer material can be further determined. The purpose of this is to keep the overall structure intact in actual operation and meet the expected functions.

[0114] Next, the process of depositing the fluoropolymer middle layer of the present invention is described. The process of depositing the fluoropolymer middle layer involves several key steps to ensure the friction resistance and ice resistance of the final coating. The first task is to use vapor deposition technology to create a uniformly covered coating. This process requires fine control of the gas composition and temperature to stabilize the deposition rate and avoid microcracks or cracks caused by uneven accumulation of materials. For example, in a specific application scenario, the fluoropolymer material is evaporated and deposited onto the substrate by heating under a low pressure environment to ensure that the fluoropolymer can be smoothly coated without aggregation or cracking.

[0115] Next, in order to further improve the performance of the coating, it is necessary to control the concentration of the fluoropolymer solution used during spraying. In particular, RF is achieved by adjusting the mixing ratio of fluoropolymer and solvent. This parameter is expressed as the ratio of the solute (i.e., fluoropolymer) to the total mass of the solution. When this ratio exceeds a certain set threshold, the water absorption rate of the final product under wet conditions can be effectively reduced. For example, if the mass ratio of fluoropolymer to solvent is set at a specific ratio RF, if this value is set appropriately (for example, adjusted according to the specific chemical properties of the polymer and the desired anti-icing effect), the ability of the coating to repel moisture can be enhanced, thereby reducing the possibility of frost adhesion.

[0116] The next step is to rapidly heat cure the deposited coating at high temperature. High temperature helps to accelerate the chemical cross-linking between fluoropolymer materials, strengthen the physical bonding, make the coating stronger and have stronger mechanical strength. A specific example may be a setting that quickly increases and maintains a constant temperature within a certain time range (for example, a suitable point can be selected between 150°C and 300°C as the curing operating temperature). Such heat treatment can promote the mutual binding between molecules.

[0117] The final step is to further enhance the hydrophobic and wear-resistant qualities of the surface by utilizing the properties of high temperature and fluorine-containing elements. The molecular structure of fluorine-containing materials tends to repel liquids, a property that is enhanced under controlled temperature treatment and helps reduce wear and tear in daily use. Specifically, fluorine atoms can be more effectively arranged on the surface of the material in a high temperature environment, forming an inherent anti-stick and anti-slip property, providing excellent surface protection. These steps together constitute a complete coating process and ensure that the manufactured surface has the best quality of friction resistance and protection against frost deposition.

[0118] Next, the process of setting the nano-microstructure upper layer enhancement of the present invention is described in detail. The first step is to optimize the surface friction based on the nanoparticle embedding technology to enhance the wear resistance NWD, that is, to increase the wear resistance of the material surface by embedding nano-scale particles; this technology can effectively improve the surface wear resistance of the coating by controlling the particle distribution density; when it is detected that the NWD is lower than a predetermined target wear resistance value, the number and concentration of embedded particles are adjusted and increased to improve the wear resistance; for example, in the preparation of a scratch-resistant and anti-icing coating for the exterior of an automobile, it was found that the NWD value of the coating under the original configuration was 2.5kg / cm 2 If the pressure is too high, it should be adjusted to a value higher than the target value, such as 4 kg / cm 2 .

[0119] Continuing the process, a nanopore network is formed to strengthen the microscopic roughness of the coating, increasing the physical and mechanical grip points to resist wear while also increasing the surface area of ​​the chemical reaction, which is beneficial to further enhance the anti-ice and snow function; a specific example is that after producing a coating used for aviation parts, in this step, the roughness coefficient is increased by manufacturing a pore network within a specific density and depth range (such as between 50nm-100nm) to enhance the anti-scratch performance.

[0120] Evaporation of nano-scale thin films improves the peeling resistance of the upper layer; this step involves attaching nanoparticles or molecules to the coating by evaporation under vacuum, making the top layer tighter and less likely to peel off; in one embodiment, if the coating on the surface of the aircraft is exposed to severe weather conditions such as hail or strong winds, it should be ensured that its outer coating has a stronger bonding force to prevent it from falling off. This process can use an evaporation source to evaporate and condense silver particles on the surface of the coating to ensure that the film thickness is stable and reaches the optimal 1-2nm.

[0121] The last step is to use pulsed laser deposition to prepare a porous surface with a high-resolution geometric structure. Through precise positioning and energy release, various micro-nano materials can be accurately deposited at specific locations to construct complex structures; the coating formed in this way has a high degree of dimensional accuracy and structural complexity, which can significantly reduce the contact area between the coating and ice; for example, when manufacturing surface protection for outdoor electronic devices, multi-scale grooves or protrusions can be generated in selected areas through pulsed laser deposition technology, so that the surface of the equipment is not easily fixed by ice and snow; and when setting the structure, the morphological parameters that are most conducive to reducing viscosity should be selected according to the adhesion characteristics of ice, such as setting the boss spacing and size between about 2-5μm.

[0122] The method for preparing a friction-resistant anti-icing coating of the present invention includes the following series of precisely designed processes to effectively cope with a series of challenges faced by the coating under extreme conditions, such as extreme cold, moisture erosion, and technical difficulties caused by repeated physical actions.

[0123] The preparation process begins with a surface pretreatment step, where the substrate is cleaned and activated by using appropriate technical means, thereby enhancing the adhesion between the coating and the substrate. Then, a self-healing bottom layer is formed. This special bottom layer can automatically heal cracks when the coating surface is slightly damaged, significantly improving the ability of the anti-icing coating to resist crack propagation caused by material embrittlement under extreme cold conditions.

[0124] A hydrophobic fluoropolymer middle layer is further applied on top of the self-healing base layer. This polymer layer can effectively prevent moisture from penetrating into the coating, reducing the risk of reduced adhesion of the coating in high humidity environments. At the same time, this layer gives the entire coating system excellent hydrophobicity, improves the ability to repel ice and snow, and helps mitigate damage caused by repeated freezing and thawing.

[0125] The final stage of the process is to set a nano-scale microstructure on the surface as an upper layer to further improve the mechanical properties of the system and enhance its anti-adhesion performance to ice. The presence of this layer also enhances wear resistance and durability, effectively preventing the durability from being reduced during high-frequency rapid friction processes.

[0126] In general, the coating system of this patent uses a multi-level strategy, including the self-repair mechanism of the bottom layer, the effective isolation of the middle layer from the environmental moisture, and the design of the surface structure to resist physical stress, which comprehensively solves the multiple functional degradation and technical difficulties that may occur when the coating faces complex conditions (cracks caused by low-temperature embrittlement, adhesion failure caused by excessive humidity, separation of materials during repeated temperature changes, and performance degradation caused by aging and wear under the action of ultraviolet rays). Such a structural design provides an innovative solution for the application of long-life coatings in harsh operating environments.

[0127] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit thereof, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a friction-resistant anti-icing coating, characterized in that: It includes the following steps: S1: Obtain a clean and activated substrate based on surface pretreatment; S2: Form a bottom layer with self-healing function; S3: Deposit a fluoropolymer middle layer to provide hydrophobicity; S4: Set an upper layer of nano-microstructure to enhance mechanical properties and anti-ice adhesion.

2. The method for preparing a friction-resistant anti-icing coating according to claim 1, characterized in that: The specific steps for obtaining a clean and activated substrate based on surface pretreatment include: S101: Clean the substrate to remove contaminants; S102: Mechanically polish or chemically treat the substrate surface to activate the surface; S103: Further clean and roughen the surface by sandblasting to improve the adhesion of subsequent coatings; S104: Preheat the substrate to temperature T1, where T1 is between the ambient temperature Tamb and the critical temperature Tc, ensuring T1 < Tc. Here, T1 refers to the preheating temperature, and Tc refers to the temperature threshold to avoid the material from starting to soften or deform due to overheating, which helps prevent crack propagation caused by increased brittleness of the coating material at extremely low temperatures.

3. The method for preparing a friction-resistant anti-icing coating according to claim 2, characterized in that: The sandblasting process in the surface pretreatment includes: A1: Use particles with an average particle size d1, and the particle size is controlled within the range of dmin to dmax, where 2mm ≤ dmin ≤ d1, and dmax = 2 * d1; A2: Set the pressure P of the compressed air to be adjusted between 1 and 2 atmospheres to control the impact speed; A3: Adjust the distance between the abrasive and the substrate to D; A4: The ratio of d1 / P is adjusted to ensure an appropriate abrasive erosion rate to optimize the surface texture. This ratio should satisfy the condition d1 / P ≤ dmax * D / (Tc - Tamb), and this formula is used to calculate the proportional relationship between the particle size and the compressed air pressure during sandblasting to achieve the most suitable coating pretreatment effect under different ambient temperature conditions.

4. The method for preparing a friction-resistant anti-icing coating according to claim 3, characterized in that: The steps for selecting the sandblasting medium during sandblasting include: Select suitable hard particles according to the material; Prevent moisture condensation by measuring and ensuring that the dew point temperature of the compressed air is below zero; Pre-dry the abrasive to remove impurities and ensure its purity.

5. The method for preparing a friction-resistant anti-icing coating according to claim 4, characterized in that: The correlation coefficients based on adjusting the water content of the compressed air and the particle size include: Control the particle spraying rate so that the thickness of the coating per unit area covered each time remains consistent; Adjust the air cooling time and frequency to ensure stress release during the pretreatment process to prevent cracking; Detect the relative humidity of the air to adjust the water content ratio in the sandblasting material and the compressed air in real time; Define the correlation conditions between X and Z to make the compressed air quality level higher than a specific level S.

6. The method for preparing a friction-resistant anti-icing coating according to claim 1, characterized in that: The process of obtaining a clean and activated substrate based on surface pretreatment includes: Ultrasonic cleaning to remove impurities on the substrate surface; Use pickling or alkali washing treatment to improve surface activity; Adopt plasma treatment to enhance the adhesion of the substrate; and Dry at a temperature below 50 degrees Celsius to prevent recontamination of the surface.

7. The method for preparing a friction-resistant anti-icing coating according to claim 1, characterized in that: The process of forming a bottom layer with self-healing function includes: Based on the coating of polyurea elastomer to achieve the ability of the coating to automatically restore broken bonds; Mix in reversible cross-linking monomers to enhance the ductility of the material at low temperatures; Add UV stabilizers to resist the breaking of chemical bonds under light.

8. The method for preparing a friction-resistant anti-icing coating according to claim 1, characterized in that: During the process of depositing the fluoropolymer middle layer, it includes: Use a vapor deposition process to ensure a uniform coating and reduce irregular cracks; Adjust the ratio RF of fluoropolymer to solvent during spraying (RF stands for Ratio of Fluoropolymer to Solvent). When RF> the set ratio threshold, the water absorption is reduced. High temperature rapid curing of coatings to improve mechanical strength; The characteristics of fluorine atoms are used under high temperature conditions to improve the wear resistance and hydrophobicity of the surface.

9. The method for preparing a friction-resistant anti-icing coating according to claim 1, characterized in that: The process of setting the nano-microstructure upper layer enhancement specifically includes: Based on nanoparticle embedding technology, the surface friction is optimized to enhance the wear resistance NWD (NWD refers to NanoWearDurability). When NWD < target wear resistance value, the distribution concentration of particles needs to be increased to improve wear resistance; Forming a nanoporous network to enhance microscopic roughness; Evaporation of nano-scale thin films improves the peeling strength of the upper layer; Pulsed laser deposition is used to prepare surface topologies with complex structures, multiple pores and highly controllable size characteristics, thereby effectively reducing ice viscosity.